Costs and benefits of forest management certifikation for Polish State Forests under Forest Stewardship Council scheme - Romaniuk, Bozena (SLU/Southern Swedish Forest Research Centre, 2008)
The thesis presents results and analysis of investigation conducted in four regional directorates of Polish State Forests and twelve forest districts (three in each directorate). The survey was done in autumn 2007. The main aim of the study was to find an answer for query "What are the costs and benefits of forest certification for Polish State Forests." To be précised in investigation – costs of forest certification as well as certification benefits have been divided into direct and indirect. Direct costs are connected with audit carried out in forest districts annually or every 5 years. Into indirect certification costs were included: social costs (e.g. connected with forest workers safety), extra bureaucracy work, amendments in forest management and nature costs (as dead wood left in forests, set aside areas or trees retained in forest after cuttings). Direct benefits: price premium and additional sale. Indirect benefits were divided into monetary and non-monetary. The annual direct costs per hectare range from 0.019 EUR in Białystok Regional Directorate to 0.043 EUR in Łódź Regional Directorate. Costs per hectare decrease together with increase in the considered area. Indirect Forest Certification (FC) costs connected with e.g. set aside areas or forest management improvements and other activities were nowhere to find. Roughly estimated, the highest obtained indirect costs (nature costs) are equal to almost 400 000 EUR. Such assessment was possible to make in Poznań RD case, where certificate was suspended because of too small extent of set aside areas (2% instead of required 5%). The estimated social and bureaucracy costs (average for regional directorate) amounted to around 90 000 EUR per year.